Teachers Intention to Use E-Learning During The Covid-19 Pandemic: Age and Gender Perspective - Kardoyo; Kusumantoro; Nurkhin, Ahmad; Mukhibad, Hasan (Jurnal Pendidikan Indonesia, 2022)
During the Covid-19 pandemic, learning was carried out online using an e-learning system. With this system, all students and teachers can even carry out learning even though they are at home. This study aims to analyze teachers' intentions in using e-learning during the covid-19 pandemic. This study uses a modified model of TAM (Technology Acceptance Model). This study uses 7 Likert scales in measuring all indicators. The data analysis method uses Structured Equation Models (SEM). The results of the study show that perceived ease of use (USE) has a significant effect on teacher intentions in utilizing e-learning, while perceived ease of use (EASE) has no significant effect on the use of e-learning. Gender was not proven to be a moderating variable on the relationship between USE and EASE with teachers' intentions to use e-learning. Teacher age strengthens the USE relationship to e-learning use. However, teacher age weakens the relationship between EASE and e-learning use. Male and female teachers have the same understanding regarding e-learning. In addition, teachers with a more mature age see e-learning as a system that provides benefits for them to carry out their duties as teachers. They also focus more on improving performance. On the other hand, teachers with more mature ages are less concerned about the ease of using e-learning.